Avaliação da eficiência térmica de telha reciclada à base de embalagens longa vida - Fiorelli, Juliano [UNESP]; Morceli, José A. B. [UNESP]; Vaz, Rodrigo I. [UNESP]; Dias, Antonio A. (Departamento de Engenharia Agrícola - UFCG, 2009)
This paper presents a study of the influence of roof tiles made of recycled long-life packaging (brand-name IBAPLAC®) on the thermal comfort of zootechnical facilities. The research was conducted at UNESP's Experimental Campus at Dracena, State of São Paulo, Brazil. Four prototypes were built, each with an area of 28 m². One prototype was covered with roof tiles made of recycled long-life packing material and three reference prototypes were roofed with ceramic tiles, ceramic tiles painted white and fiber/cement tiles (Brasilit®), respectively. Black globe thermometers and dry and wet bulb thermometers were installed inside the prototypes. Temperatures inside the structures were recorded in the Summer of 2006/2007 over a 90-day period. A descriptive statistical analysis was made, based on the mean values of black globe temperature and humidity index, radiant thermal load and temperature-humidity index of the period. The results obtained indicated that the thermal behavior of the recycled tile was similar to that of the ceramic tiles.

Neste trabalho se apresenta o estudo da influência de telha reciclada à base de embalagens longa vida (IBAPLAC®) no conforto térmico de instalações zootécnicas. A pesquisa foi desenvolvida no Campus Experimental da Unesp de Dracena, SP. Foram construídos quatro protótipos, com área de 28 m² cada um, sendo um deles coberto com telha reciclada à base de embalagens longa vida e três protótipos de referência cobertos com telha cerâmica, telha cerâmica pintada de branco e telha de fibrocimento (Brasilit®). Dentro dos protótipos foram instalados termômetros de globo negro e termômetros de bulbo seco e bulbo úmido. Os dados foram coletados no verão de 2006/2007, totalizando 90 dias. Uma análise estatística por inferência e descritiva foi realizada utilizando-se valores médios de índice de temperatura de globo e umidade, carga térmica radiante e índice de temperatura e umidade, referente ao período. Pelos resultados obtidos é possível afirmar que a telha reciclada apresentou índices de conforto térmico semelhantes àqueles encontrados para as telhas cerâmicas, podendo ser indicada como opção de cobertura para instalações zootécnicas.
Evaluation of the thermal efficiency of roof tiles made of recycled long-life packaging
Keywords: ambiance; roofing; thermal environment indexes; ambiência; cobertura; índices do ambiente térmico